Endovascular management of radial artery loop for neuroangiography: Case series. Issue 4 (August 2021) - Dossani, Rimal H; Waqas, Muhammad; Tso, Michael K; Cappuzzo, Justin M; Popoola, Daniel; Snyder, Kenneth V; Levy, Elad I; Siddiqui, Adnan H; Davies, Jason M
Background: Radial loops are rare congenital radial artery anomalies that may pose a significant challenge to successful transradial neuroangiography. In this case series, we describe the anatomy and frequency of radial artery loops and provide a technique for successful navigation of this anatomic anomaly. Methods: We reviewed our database of radial diagnostic or interventional neuroangiographic procedures to identify cases in which a radial loop was encountered during the procedure. The loop pattern, the presence of an associated recurrent radial artery branch, navigation technique, and procedure-related complications were recorded. A descriptive analysis was performed. Results: A total of 997 transradial approach procedures were performed over a 9-month period. A radial loop was identified in 10 (1.0%) patients. The average age was 68.6 ± 14.3 years. A microcatheter advanced over a microwire was used to navigate the loop and avoid entry into the recurrent branch. A diagnostic neuroangiographic procedure was performed successfully in 8 cases and an intervention was performed successfully in 1 case. A 360° loop was present in 2 of these cases. In each case, transradial access was performed successfully. In 1 other diagnostic case, transradial access was aborted, and the femoral artery was accessed to perform the procedure. Conclusions: A radial loop was present in 1% of the cases in this series. Our technical results suggest that this anomaly should not be considered a contraindication to transradial neuroangiography because the procedure was successfully performed in most (9 of 10) cases using a microcatheter system to navigate the loop.